Omnichannel fulfillment and item-level RFID tracking in fashion retailing - Ovezmyradov, Berdymyrat; Kurata, Hisashi (Computers & industrial engineering, 2022)
•Model of supply chain with item-level RFID tracking in a fashion store.•Responses to stockout and item-level tracking can reduce inventory.•Shrinkage, interest rate, backorder, brand and store switching affect RFID investment.•Item-level RFID tracking is highly relevant in omnichannel fashion retailing. Practitioners have long known that item-level tracking of products with the aid of radio frequency identification (RFID) has an exceptionally high potential for application with omnichannel fulfillment. Investments in both RFID and omnichannel expanded, but there was a lack of studies to assess their benefits. The introduction of omnichannel retailing is a big challenge for managers since it demands higher stocking levels due to the higher shrinkage cost. This research focuses on modeling one of the promising RFID applications: in-store merchandise tracking on item level. This model shows how a combination of consumers' response to stockout in omnichannel retailing coupled with item-level RFID tracking ensures inventory reduction, leading to higher on-shelf availability and lower cost. Thus, a modeling approach allows defining the value of the costly investment in the in-store location tracking in omnichannel fulfillment. A comparison is made between three scenarios: no-omnichannel and no-RFID; omnichannel without RFID; and omnichannel with RFID. In addition, this study examines under which parameters of costs, backlogging, brand and store switching, and other conditions one scenario could be more profitable for a retailer than another. The main finding of the study suggests the retailer's profitability could increase significantly as a result of the combined effect of investment in omnichannel fulfillment and item-level RFID. At the same time, the optimal inventory could be reduced. This study supports evidence of the higher return on investment in item-level RFID tracking of fashion products in omnichannel retailing.